DINAMIKA TAFSIR SOSIAL INDONESIA - Sunarto Sunarto (Institut PTIQ Jakarta, 2019)
The Qur'an is a holy book that revealed by the Most Holy. In order for the sanctity of the Qur'an to be more meaningful and relevant to (as a guide for human life, as a distinguishing between the true and the false), the Qur'an needs to be reflected in the real world. With the presence of